Assessing Adipogenic Potential of Mesenchymal Stem Cells: A Rapid Three-Dimensional Culture Screening Technique - Jean F. Welter; Kitsie J. Penick; Luis A. Solchaga (Hindawi Limited, 2013)
Bone-marrow-derived mesenchymal stem cells (MSCs) have the potential to differentiate into a number of phenotypes, including adipocytes. Adipogenic differentiation has traditionally been performed in monolayer culture, and, while the expression of a fat-cell phenotype can be achieved, this culture method is labor and material intensive and results in only small numbers of fragile adherent cells, which are not very useful for further applications. Aggregate culture is a cell-culture technique in which cells are induced to form three-dimensional aggregates; this method has previously been used successfully, among others, to induce and study chondrogenic differentiation of MSCs. We have previously published an adaptation of the chondrogenic aggregate culture method to a 96-well plate format. Based on the success of this method, we have used the same format for the preparation of three-dimensional adipogenic cultures. The MSCs differentiate rapidly, the aggregates can be handled and processed for histologic and biochemical assays with ease, and the format offers significant savings in supplies and labor. As a differentiation assay, this method can distinguish between degrees of senescence and appears suitable for testing medium or drug formulations in a high-volume, high-throughput fashion.